Fibonacci sums modulo 5 - Adegoke, Kunle; Frontczak, Robert; Goy, Taras (Annales Mathematicae Silesianae, 2024)
We develop closed form expressions for various finite binomial Fibonacci and Lucas sums depending on the modulo 5 nature of the upper summation limit. Our expressions are inferred from some trigonometric identities.